Maternal mortality report (London : The Maternal Mortality Committee)
1934-10 1934 1930s 19 pages In a very comprehensive report from Lindsey, Lincolnshire, the Medical Officer says that arrangements for ante-natal supervision in villages are very incomplete. Where an ante-natal clinic is not within a reasonable distance it has been decided that each patient in a midwife's practice should be examined as a routine measure by the local medical practitioner in the presence of the midwife and a report made of any abnormality observed and any ante-natal treatment thought necessary. The County Medical Officer for Buckinghamshire records that the difficulties of ante-natal treatment in rural areas have increased owing to financial depression and need for economy. Dr. Ashworth, of the Boston Welfare Centre, says: "It is regrettable that no provision has been made for ante-natal work in this large area. The midwives have frequently expressed a desire for a clinic as their heavy district work prevents them from doing much ante-natal work." The Warwickshire County Medical Officer notes that attendances at ante-natal clinics merely touch a fringe of an important service. The development of clinics, he suggests, must inevitably be slow and restricted. The Medical Officers in many cases maintain that the family doctor should be approached by the midwife for ante-natal care, but often complain that they cannot secure the co-operation of the general practitioner. The Medical Officer for Cumberland says, in regard to the increase in the number of ante-natal examinations by general practitioners, that it is more desirable that an examination be made by the practitioner who is likely to be called in at the confinement in the event of a difficulty, rather than by a wholetime officer of the Authority who will not be present. It is also encouraging to find that more interest is apparently being taken in post-natal work. A large number of Medical Officers of Health deplore the continued high maternal death rate and press for a better service. It is pleasing to note throughout the reports that the standard of ante-natal work by the midwives has improved. The Medical Officer for Newport, Mon., says that "the majority of the midwives devote more care to their patients' health during pregnancy than was the custom in former years. This additional supervision is demanded by the Central Midwives Board, but the midwife is not recompensed for her ante-natal care. Several if not all of the midwives are finding it increasingly difficult to obtain their full fees from their patients, although the patients are in receipt of the Maternity Benefit allowance under the National Health Insurance Scheme." A tribute is paid to the co-operation of the midwives by the Medical Officer for Oxford who says : "The (ante-natal and post- (13) 292/824/1/20